Active control of a three-story building using hedge-algebras-based fuzzy controller - Le, Bui Hai (Vietnam Journal of Mechanics, 2011)
In this paper, conventional and hedge-algebras-based fuzzy controllers, respectively denoted by FC and HAFC, are designed to suppress vibrations of a three-story building against earthquake. The structural system is simulated against the ground accelerations of the El Centro earthquake in USA on May 18th, 1940; the Northridge earthquake in USA on January 17th, 1994 and the Kobe earthquake in Japan on January 16th, 1995. The control effects of FC and HAFC are compared via the time history of the story displacements of the structure.